Composites of Wood and Biodegradable Thermoplastics: A Review. (3rd July 2018) - Chan, Clement Matthew; Vandi, Luigi-Jules; Pratt, Steven; Halley, Peter; Richardson, Desmond; Werker, Alan; Laycock, Bronwyn
ABSTRACT: This paper is an overview of current understanding in the areas of composites made from biodegradable thermoplastics and wood fillers. The review finds that the composite properties depend on the type of wood filler, the choice of polymer matrix, the wood filler content, the compatibilization technique used and the processing parameters. The extent of interfacial adhesion and the filler morphology are identified as the underlying factors that control the composite properties. Future research needs are identified, including establishment of fundamental relationships between quantified interfacial adhesion and end-use properties and advanced modelling of biodegradation processes.